Appendiceal neurofibroma in a patient with neurofibromatosis 1 and recurrent abdominal infections from ventriculoperitoneal shunt: a case report. Issue 4 (19th April 2021) - Greenberg, Anya L; Choi, Won-Tak; Shaked, Oren; Lee, Anthony T; Berrahou, Iman K; Jacques, Line G; Lebares, Carter C
Abstract: Appendiceal neurofibromas are exceedingly rare, with neither experimental nor observational data to support evidence-based diagnosis or treatment. We describe the case of a 52-year-old woman with neurofibromatosis 1 (NF1) complicated by aqueductal stenosis and resultant hydrocephalus needing a ventriculoperitoneal shunt (VPS). She presented to the emergency department with abdominal pain and was found to have abnormalities in the right hemiabdomen on cross-section imaging, also a Staphylococcus epidermidis growth at the distal portion of the VPS. She was initially treated with two rounds of intravenous antibiotics and VPS removal without improvement. She ultimately underwent an appendectomy, which revealed pathologic evidence of NF. The appendectomy was key to ruling out malignancy, addressing further symptoms and preventing future malignant transformation. This case highlights the importance of including appendiceal neurofibromas in the differential diagnoses of abdominal pain in patients with NF1.